2022
DOI: 10.1097/pec.0000000000002879
|View full text |Cite
|
Sign up to set email alerts
|

Redirecting Nonurgent Patients From the Pediatric Emergency Department to Their Pediatrician Office for a Same-Day Visit—A Quality Improvement Initiative

Abstract: Objectives: Providing high-quality care in the appropriate setting to optimize value is a worthy goal of an efficient health system. Consequences of managing nonurgent complaints in the emergency department (ED) have been described including inefficiency, loss of the primary care-patient relationship, and delayed care for other ED patients. The purpose of this initiative was to redirect nonurgent patients arriving in the ED to their primary care office for a same-day visit, and the SMARTAIM was to increase red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The QI project was implemented in a pediatric ED that serves as primary and urgent care for many families. Recent studies have identified this common pattern of pediatric ED use for nonurgent conditions (Frazier et al, 2022;Li et al, 2022;Wolski et al, 2022). The ED represents a prime opportunity to screen families for CPS needs, as they may not receive important anticipatory guidance surrounding injury prevention education in the primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…The QI project was implemented in a pediatric ED that serves as primary and urgent care for many families. Recent studies have identified this common pattern of pediatric ED use for nonurgent conditions (Frazier et al, 2022;Li et al, 2022;Wolski et al, 2022). The ED represents a prime opportunity to screen families for CPS needs, as they may not receive important anticipatory guidance surrounding injury prevention education in the primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increasing number of behavioral health boarders, pediatric EDs have faced fluctuations in patient volumes due to the SARS‐CoV‐19 pandemic and novel bacterial and viral transmission patterns 16,31–33 . To address these recent trends, new clinical care models have been developed including alternative care sites 13,18,19,34 . To date, no studies have examined the impact that these trends and resulting changes in clinical operations have on patient exposure during residency training.…”
Section: Discussionmentioning
confidence: 99%
“…16,[31][32][33] To address these recent trends, new clinical care models have been developed including alternative care sites. 13,18,19,34 To date, no studies have examined the impact that these trends and resulting changes in clinical operations have on patient exposure during residency training. While there is no ability to ensure clinical exposure translates to competency, clinical care is a core part of training.…”
Section: Not Estimablementioning
confidence: 99%
See 2 more Smart Citations